Unexpected Interference of the Triethanolamine Sacrificial Electron Donor with the Excited States of Molecular and Heterogenized Rhodium Bipyridine Photocatalysts Revealed by Femtosecond Transient Absorption Spectroscopy - Perrinet, Quentin; Ghosh, Ashta C.; Canivet, Jérôme; Wisser, Florian; Roland, Thomas; De Waele, Vincent (Journal of Physical Chemistry C, 2025)
Molecular and heterogenized rhodium bipyridine (Bpy) complexes are highly active and selective for carbon dioxide photoreduction into formic acid using visible light as the sole energy source. The excited states of the molecular 5,5′-di(pyren-1-yl)-2,2′-bipyridine Pyr2Bpy and of the corresponding conjugated microporous polymer PyrBpy-CMP, envisioned as a macroligand, as well as of their organometallic complexes with pentamethylcyclopentadienyl (Cp*) rhodium [Pyr2Bpy]Cp*RhCl2 and Cp*Rh@PyrBpy-CMP have been investigated by femtosecond UV-vis transient absorption spectroscopy. In both polymers PyrBpy-CMP and Cp*Rh@PyrBpy-CMP, the fs measurements reveal the formation of broad excited-state absorption bands decaying in the subnanosecond time scale. For Cp*Rh@PyrBpy-CMP, the ultrafast energy transfer from the framework to the catalytic centers is demonstrated. Pyr2Bpy and [Pyr2Bpy]Cp*RhCl2 have been studied as model molecular building blocks of the CMP. The results show the participation of a mesomeric intramolecular charge transfer (MICT) state and of a twisted intramolecular charge transfer (TICT) state stabilized by the torsion of the pyrene and bipyridine moieties, which are then converted into ligand-to-metal charge transfer (LMCT) states in [Pyr2Bpy]Cp*RhCl2. The photophysical parameters determined for the molecular compounds were applied to calculate the Förster resonance energy transfer rate from the light-harvesting organic units to the heterogenized Rh metal centers. Finally, the unexpected role of triethanolamine, a common sacrificial electron donor (SED) employed for CO2 reduction, as an efficient quencher of the excited states of the Pyr2Bpy is revealed. This quenching reaction is expected to occur for a wide range of organic and organometallic photocatalysts, and its consequences on the reduction of the photoconversion yield are certainly underestimated for most photocatalytic applications.
CRIS-Team Scopus Importer:2025-01-31